Resistência na casa grande: história e cultura afro-brasileira na educação de adultos - Silva, Neide Cristina da (2013)
This present study, entitled Resistance in the big house: history and culture African-Brazilian in adult education , had as a target to investigate and analyze whether and how the students call themselves as black, in Adult Education in Tiradentes City, were impacted with the study of the History and Afro-Brazilian Culture. The issue which encouraged this research was the negative vision that the black student of EDA sees about him/herself and about his/hers colleagues, due to a devaluation of their origin and culture. The hypothesis presented is that, as Tirantes City is a district formed mostly by black people and its inhabitants are, constantly, discriminated, the introduction of the History and Culture Afro-Brazilian discipline promotes awareness and criticalness, besides being an instrument of awareness of blackness of the EDA High School learners. Regarding the methods and procedures, at first it was used an exploratory research and bibliographic that allowed to get the information already cataloged. In the second phase, it was performed a field study that sought to draw a profile of the EDA students and to confirm or to deny the hypothesis. The analysis and the interpretation used the categories Alienation and Awareness, having as a reference the work of the educator Paulo Freire. The results indicate that the majority of students are women, the predominant age is between 18 to 25 years, ( 66% ) call themselves black, they have low professional qualification and low-income. Regarding to African-Brazilian studies, there is also whom still persists the approach of the black as a slave and subaltern, but as the path is made by walking , there are significant approaches in the Tiradentes City, that are instruments of the awareness from their students.